STRATEGY FOR THE TRAINING OF HIGHLY QUALIFIED SCIENTIFIC PERSONNEL AT THE NATIONAL AVIATION UNIVERSITY - Kharchenko, Volodymyr; Prusov, Dmitry (Proceedings of National Aviation University (archive), 2014)
The new strategy for the training of highly qualified scientific personnel at the National AviationUniversity has been considered due to the european third-cycle engineering education within the framework theInternational Tempus-Project implementation "New Model of the Third Cycle in Engineering Education due to BolognaProcess" (NETCENG).